Carotid Intima‐Media Thickness but Not Carotid Artery Plaque in Healthy Individuals Is Linked to Lean Body Mass. Issue 15 (6th August 2019) - Arnold, Matthew; Linden, Andrew; Clarke, Robert; Guo, Yu; Du, Huaidong; Bian, Zheng; Wan, Eric; Yang, Meng; Wang, Liang; Chen, Yuexin; Chen, Jianwei; Long, Huajun; et al.
Abstract : Background: Lean body mass has been identified as a key determinant of left ventricular mass and wall thickness. However, the importance of lean body mass or other body‐size measures as normative determinants of carotid intima‐media thickness (cIMT), a widely used early indicator of atherosclerosis, has not been well established. Methods and Results: Carotid artery ultrasound measurements of cIMT and carotid artery plaque burden (derived from plaque number and maximum size) and measurements of body size, including height, body mass index, weight, body fat proportion, and lean body mass ([1−body fat proportion]×weight), were recorded in 25 020 participants from 10 regions of China. Analyses were restricted to a healthy younger subset (n=6617) defined as never or long‐term ex‐regular smokers aged <60 years (mean age, 50) without previous ischemic heart disease, stroke, diabetes mellitus, or hypertension and with plasma non‐high‐density lipoprotein cholesterol <4 mmol/L. Among these 6617 participants, 86% were women (because most men smoked) and 9% had carotid artery plaque. In both women and men separately, lean body mass was strongly positively associated with cIMT, but was not associated with plaque burden: overall, each 10 kg higher lean body mass was associated with a 0.03 (95% CI, 0.03–0.04) mm higher cIMT ( P =5×10 −33 ). Fat mass, height, and other body‐size measures were more weakly associated with cIMT. Conclusions: The strong association of lean body mass with cIMT, but not with plaque burden, in healthy adults suggests a normative relationship rather than reflecting atherosclerotic pathology. Common mechanisms may underlie the associations of lean body mass with cIMT and with nonatherosclerotic vascular traits.